Facile green synthesis of BCN nanosheets as high-performance electrode material for electrochemical energy storage - Karbhal, Indrapal; Devarapalli, Rami Reddy; Debgupta, Joyashish; Pillai, Vijayamohanan K.; Ajayan, Pulickel M.; Shelke, Manjusha V. (Chemistry-A European Journal, 2016)
Two-dimensional hexagonal boron carbon nitride (BCN) nanosheets (NSs) were synthesized by new approach in which a mixture of glucose and an adduct of boric acid (H3BO3) and urea (NH2CONH2) is heated at 900 degrees C. The method is green, scalable and gives a high yield of BCN NSs with average size of about 1 mm and thickness of about 13 nm. Structural characterization of the as-synthesized material was carried out by several techniques, and its energy-storage properties were evaluated electrochemically. The material showed excellent capacitive behaviour with a specific capacitance as high as 244 F g(-1) at a current density of 1 A g(-1). The material retains up to 96% of its initial capacity after 3000 cycles at a current density of 5 A g(-1).
Keywords: boron; Doping; Electrochemistry; Nanoparticles; nitrides

Sunlight assisted degradation of dye molecules and reduction of toxic Cr(VI) in aqueous medium using magnetically recoverable Fe3O4/reduced graphene oxide nanocomposite - Boruah, Purna K.; Borthakur, Priyakshree; Darabdhara, Gitashree; Kamaja, Chaitanya Krishna; Karbhal, Indrapal; Shelke, Manjusha V.; Phukan, Pallabi; Saikia, Dulen; Das, Manash R. (RSC Advances, 2016)
In view of the significant impact of magnetically recoverable catalysts in photocatalytic applications, Fe3O4/reduced graphene oxide (rGO) nanocomposite photocatalyst was synthesized by adopting an eco-friendly solution chemistry approach and has been characterized by high resolution transmission electron microscopy (HRTEM), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy and photoluminescence (PL) spectroscopy. Fe3O4/rGO nanocomposite is efficiently utilized towards photocatalytic degradation of carcinogenic and mutagenic cationic as well as anionic dye molecules namely methyl green (MG), methyl blue (MB) and rhodamine B (RhB) under direct sunlight irradiation. The Fe3O4/rGO nanocomposite also demonstrated excellent photocatalytic reduction of aqueous Cr(VI) solution to nontoxic aqueous Cr(III) solution of more than 96% within 25 min under sunlight irradiation. Moreover, reusability of the magnetically recovered photocatalyst was studied efficiently up to 10 cycles in the degradation process. The catalyst was also characterized after the degradation of the dye molecule and the particle size of the Fe3O4 nanoparticles on the rGO sheets remained unchanged. The present investigation focuses on the importance of the use of Fe3O4/rGO nanocomposite towards photocatalytic degradation of waste water containing organic dye pollutants and toxic Cr(VI), as an easily recoverable and reusable photocatalyst with potential for many environmental remediation applications.

Ammonia-modified graphene sheets decorated with magnetic Fe3O4 nanoparticles for the photocatalytic and photo-Fenton degradation of phenolic compounds under sunlight irradiation - Boruah, Purna K.; Sharma, Bhagyasmeeta; Karbhal, Indrapal; Shelke, Manjusha V.; Das, Manash R. (Journal of hazardous materials, 2017)
Synthesis of easily separable and eco-friendly efficient catalyst with both photocatalytic and photo-Fenton degradation properties is of great importance for environment remediation application. Herein, ammonia-modified graphene (AG) sheets decorated with Fe3O4 nanoparticles (AG/Fe3O4) as a magnetically recoverable photocatalyst by a simple in situ solution chemistry approach. First, we have functionalized graphene oxide (GO) sheets by amide functional group and then Fe3O4 nanoparticles (NPs) are doped onto the functionalized GO surface. The AG/Fe3O4 nanocomposite showed efficient photocatalytic activity towards degradation of phenol (92.43%), 2-nitrophenol (2-NP) (98%) and 2-chlorophenol (2-CP) (97.15%) within 70–120 min. Consequently, in case of photo-Fenton degradation phenomenon, 93.56% phenol, 98.76% 2-NP and 98.06% of 2-CP degradation were achieved within 50–80 min using AG/Fe3O4 nanocomposite under sunlight irradiation. The synergistic effect between amide functionalized graphene and Fe3O4 nanoparticles (NPs) enhances the photocatalytic activity by preventing the recombination rate of electron-hole-pair in Fe3O4 NPs. Furthermore, the remarkable reusability of the AG/Fe3O4 nanocomposite was observed up to ten cycles during the photocatalytic degradation of these phenolic compounds.

Facile synthesis of unique cellulose triacetate based flexible and high performance gel polymer electrolyte for lithium ion batteries - Nirmale, Trupti C.; Karbhal, Indrapal; Kalubarme, Ramchandra S.; Shelke, Manjusha V.; Varma, Anjani J.; Kale, Bharat B. (ACS Applied Materials & Interfaces, 2017)
Lithium ion batteries (LIBs) with polymer based electrolytes have attracted enormous attention due to the possibility of fabricating intrinsically safer and flexible devices. However, economical and eco-friendly sustainable technology is an oncoming challenge to fulfill the ever increasing demand. To circumvent this issue, we have developed a gel polymer electrolyte (GPE) based on renewable polymers like cellulose triacetate and poly (polyethylene glycol methacrylate) p(PEGMA) using a photo polymerization technique. Cellulose triacetate offers good mechanical strength with improved ionic conductivity, owing to its ether and carbonyl functional groups. It is observed that the presence of an open network has a critical impact on lithium ion transport. At room temperature, GPE PC exhibits an optimal ionic conductivity of 1.8 x 10(-3) S cm(-1) and transference number of 0.7. Interestingly, it affords an excellent electrochemical stability window up to 5.0 V vs Li/Li+. GPE PC shows a discharge capacity of 164 mAhg(-1) after the first cycle when evaluated in a Li/GPE/LiFePO4 cell at 0.5 C-rate. Interfacial compatibility of GPE PC with lithium metal improves the overall cycling performance. This system provides a guiding principle toward a future renewable and flexible electrolyte design for flexible LIBs (FLIBs).

Impact of rare-earth metal oxide (Eu 2 O 3 ) on the electrochemical properties of a polypyrrole/CuO polymeric composite for supercapacitor applications - Majumder, Mandira; Choudhary, Ram Bilash; Thakur, Anukul. K.; Karbhal, Indrapal (RSC Advances, 2017)
A ternary composite of polypyrrole/copper oxide/europium oxide (PPY/CuO/Eu2O3), synthesized via a facile in situ chemical oxidative polymerization method, exhibits the maximum specific capacitance of 320 F g⁻¹ at the current density of 1 A g⁻¹. Incorporation of the rare-earth metal oxide Eu2O3 in the PPY/CuO matrix can promote charge transportation in the resulting ternary nanocomposite by enhancing the porosity. The interconnected mesoporous networks reduce the internal resistance and the charge transfer resistance (Rct) of the composite electrode material. Moreover, the incorporation of Eu2O3 in the PPY/CuO provides support to the fragile polymer backbone resulting in an excellent cycle stability and a markedly enhanced thermal stability. These together with the exhibition of an excellent coulombic efficiency demonstrates that incorporation of rare earth metal oxide can play a significant role in improving the performance of a polymeric composite opted as an electrode material for high-performance supercapacitor.

Electrochemical capacitive energy storage in PolyHIPE derived nitrogen enriched hierarchical porous carbon nanosheets - Deshmukh, Ashvini B.; Nalawade, Archana C.; Karbhal, Indrapal; Qureshi, Mohammed Shadbar; Shelke, Manjusha V. (Carbon, 2018)
Porous and interconnected electrodes based on carbon nanoarchitectures offer comprehensive advantages of large specific surface area and high porosity consequently increasing the specific capacitance of ultracapacitor energy storage systems. Emulsion-templated polymers, PolyHIPEs (Polymerized High Internal Phase Emulsions) are highly porous polymers with a structure of cages interconnected by windows thus provide suitable framework to create such porous carbon nanostructures. Herein, nitrogen enriched porous carbon nanosheets are synthesized by pyrolysis of polymer-silica hybrid PolyHIPE and subsequent silica removal. This nitrogen enriched porous carbon nanosheets when tested as an electrode for ultracapacitor, showed specific capacitance as high as 209 F/g at a current density of 1 A/g in 1 M H2SO4 with excellent capacity retention over long cycling. (c) 2017 Elsevier Ltd. All rights reserved.
Keywords: Energy storage; Nitrogen enriched porous carbon nanosheets; PolyHIPE template; Ultracapacitor

Uncovering the origin of enhanced field emission properties of rGO-MnO(2)heterostructures: a synergistic experimental and computational investigation - Rondiya, Sachin R.; Karbhal, Indrapal; Jadhav, Chandradip D.; Nasane, Mamta P.; Davies, Thomas E.; Shelke, V. Manjusha; Jadkar, Sandesh R.; Chavan, Padmakar G.; Dzade, Nelson Y. (RSC Advances, 2020)
The unique structural merits of heterostructured nanomaterials including the electronic interaction, interfacial bonding and synergistic effects make them attractive for fabricating highly efficient optoelectronic devices. Herein, we report the synthesis of MnO(2)nanorods and a rGO/MnO(2)nano-heterostructure using low-cost hydrothermal and modified Hummers' methods, respectively. Detailed characterization and confirmation of the structural and morphological properties are doneviaX-ray Diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM) and Transmission Electron Microscopy (TEM). Compared to the isolated MnO(2)nanorods, the rGO/MnO(2)nano-heterostructure exhibits impressive field emission (FE) performance in terms of the low turn-on field of 1.4 V mu m(-1)for an emission current density of 10 mu A cm(-2)and a high current density of 600 mu A cm(-2)at a relatively very low applied electric field of 3.1 V mu m(-1). The isolated MnO(2)nanorods display a high turn-on field of 7.1 for an emission current density of 10 mu A cm(-2)and a low current density of 221 mu A cm(-2)at an applied field of 8.1 V mu m(-1). Besides the superior FE characteristics of the rGO/MnO(2)nano-heterostructure, the emission current remains quite stable over the continuous 2 h period of measurement. The improvement of the FE characteristics of the rGO/MnO(2)nano-heterostructure can be ascribed to the nanometric features and the lower work function (6.01 and 6.12 eV for the rGO with 8% and 16% oxygen content) compared to the isolated alpha-MnO2(100) surface (phi= 7.22 eV) as predicted from complementary first-principles electronic structure calculations based on density functional theory (DFT) methods. These results suggest that an appropriate coupling of rGO with MnO(2)nanorods would have a synergistic effect of lowering the electronic work function, resulting in a beneficial tuning of the FE characteristics.

Architecture of NaFe(MoO4)2 as a novel anode material for rechargeable lithium and sodium ion batteries - Tamboli, Asiya M.; Tamboli, Mohaseen S.; Praveen, C. S.; Dwivedi, Pravin Kumari; Karbhal, Indrapal; Gosavi, Suresh W.; Shelke, V, Manjusha; Kale, Bharat B. (Applied Surface Science, 2021)
In recent decades, particular focus has been given to enhance the capacity of LIBs and SIBs either by developing new materials or by modifying existing materials. Hence, we have demonstrated a new anode material i.e. sodium iron molybdate [NaFe(MoO4)2] for both LIBs and SIBs. NaFe(MoO4)2 has been successfully synthesized by solid-state combustion technique and tested as a promising new anode material for both LIBs and SIBs. A detailed analysis of the crystal structure has been performed using DFT calculations. NaFe(MoO4)2 crystallizes in the monoclinic phase with the space group C2/c (#15). FESEM also shows highly crystalline monoclinic shaped crystals of micron size. When evaluated as an anode material for LIBs, NaFe(MoO4)2 electrode exhibited electrochemical capacity of 920 mAhg- 1 in the second cycle at the current density of 50 mAg-1. Though capacity decreases on further cycling, the coulombic efficiency was maintained at 99% for 50 cycles. Significantly, a high discharge capacity of 100 mAhg- 1 was maintained at a very high rate of 1 Ag-1. On the other hand, we have also tested NaFe(MoO4)2 for SIBs which shows excellent reversible specific capacity i.e. 100 mAhg- 1 at the current density of 100 mAg-1 even after 500 cycles. This novel system has shown good stability for LIBs and SIBs which is hitherto unattempted.
Keywords: Electrochemical study; lithium-ion battery; Morphology; NaFe(MoO4)2; Sodium-ion battery

Engineering microstructure of LiFe(MoO4)(2) as an advanced anode material for rechargeable lithium-ion battery - Tamboli, Asiya M.; Tamboli, Mohaseen S.; Dwivedi, Pravin Kumari; Praveen, C. S.; Karbhal, Indrapal; Shelke, V, Manjusha; Kim, Bomyung; Park, Chinho; Kale, Bharat B. (Journal of Materials Science-Materials In Electronics, 2021)
Graphite is considered as an ideal anode material for lithium-ion battery (LIB) due to its high stability, good conductivity and wide source of availability. However, the low energy density and theoretical capacity of graphite cannot meet the needs of high performance anode materials. To circumvent this issue, alternative materials have been sought for many years now. Herein, we report the synthesis of highly crystalline lithium iron molybdate LiFe(MoO4)(2) by combustion method and evaluated its performance as an anode material for lithium-ion batteries. Triclinic LiFe(MoO4)(2) crystals having particle size 2-5 mu m with good crystallinity were obtained. The material shows long cycle life and high rate performance than commercial graphite and exhibits first reversible discharge capacity of 931.6 mAh/g at a current density of 100 mA/g which is three times higher than commercial graphite. The high specific capacity together with the outstanding rate and cycle performance makes LiFe(MoO4)(2) a promising anode material for LIB. A detailed analysis on the crystal structure and electronic properties of LiFe(MoO4)(2) is presented based on DFT studies to complement the experimental observations.

Laser patterning of boron carbon nitride electrodes for flexible micro-supercapacitor with remarkable electrochemical stability/capacity - Karbhal, Indrapal; Basu, Aniruddha; Patrike, Apurva; Shelke, Manjusha V. (Carbon, 2021)
High performance, all solid-state planar micro-supercapacitor (MSC) with interdigitated Boron carbon Nitride (BCN) electrodes are fabricated via fast, scalable laser patterning technique. Heteroatom doping desirably enhances the electrochemical activity of carbon electrodes. This BCN based micro-supercapacitor showed comparatively very high specific capacitance of 72 mFcm(-2) at a current density of 0.15 mAcm(-2). Even at a high current density of 1 mAcm(-2) device showed specific capacitance as high as 17 mFcm(-2). It has demonstrated excellent electrochemical stability when tested up to 80000 cycles without any sign of further decay in capacity/efficiency. This device showed stable capacity even after bending at 150 degrees angle, for 1500 times during cycling showing remarkable flexibility. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: BCN; Co-doping; Energy storage; Flexible; Laser patterning; Micro-supercapacitor

Honeycomb boron carbon nitride as high-performance anode material for li-ion batteries - Karbhal, Indrapal; Chaturvedi, Vikash; Patrike, Apurva; Yadav, Poonam; Shelke, V, Manjusha (ChemNanoMat, 2022)
3D Porous carbon-based materials are well known for their excellent mechanical and electrochemical properties for various energy storage applications including Li-ion Battery (LIB) anodes. However, their commercial application is limited due to their low theoretical specific capacity. Heteroatom doping in carbonaceous networks proved an efficient way to modify the surface properties, which considerably improves the Li intake capacity and Li diffusion in porous carbon materials. In this work, we have synthesized 3D honeycomb boron carbon nitride (HBCN) from boric acid, glucose, and cyanamide. Silica nanoparticles (SiO2 NPs) are used as structure-directing agents to replicate well-organized honeycomb structures. HBCN possesses a high specific surface area (SSA) of similar to 597 m(2) g(-1), with a uniform porosity distribution, low charge transfer resistance, and steady Li flux. When analyzed as an anode material for LIB, HBCN demonstrated an excellent specific capacity of similar to 652 mAhg(-1) and 408 mAhg(-1) at an input current density of 100 mAg(-1) and 1 Ag-1 respectively and an energy density of 227 Wh kg(-1) at 1 C rate in a full cell LIB. These results indicate that the doping of B and N hetero atoms is significantly advantageous for LIBs application.
Keywords: 3D-Architecture; Heteroatom Doping; High-Performance Anode; Honeycomb boron carbon nitride (HBCN); Li-ion battery

High rate, high temperature, dendrite free plating/stripping of Li in 3-dimensional honeycomb boron carbon nitride to realize an ultrastable lithium metal anode - Patrike, Apurva; Karbhal, Indrapal; Wasnik, Kundan; Torris, Arun; Maibam, Ashakiran; Krishnamurty, Sailaja; Shelke, V, Manjusha (Journal of Energy Storage, 2023)
Lithium (Li) metal could be the anode of choice for energy dense Li-batteries owing to its high theoretical specific capacity. However, low coulombic efficiency and poor safety on account of the occurrence of the Li-dendrites during charging-discharging pose a bottleneck for practical applications. In this work, we report a high-rate plating and stripping of Li through host engineering to realize ultrastable Li metal anode (LMA). Benchmark plating/stripping efficiency could be achieved via uniquely structured, highly ordered honeycomb boron carbon nitride (HBCN) as a functional scaffold. Boron and nitrogen doping, large surface area and ordered mesoporous structure induce homogeneous solid electrolyte interface (SEI) layer formation and provide numerous nucleation sites with subsequent dendrite-free growth with 99.98 % coulombic efficiency at 8 mA cm(-2) high current and 10 mAh cm(-2) capacity over 3000 cycles. Via post-cycling advanced characterizations techniques of Ex-situ XPS, 3D X-ray micro-tomography analyses and FESEM, we demonstrate the formation of a stable SEI layer and morphological changes that occurred during Li plating cycles in the HBCN structure. Computational studies validate the high lithium plating-stripping efficacy of HBCN to its highly ordered porous nature, exothermic Li-binding and upshift in the Fermi levels. When tested at elevated temperature (50 degrees C), a stable Li plating-stripping in HBCN is realised at 4 mA cm(-2) current and 10 mAh cm(-2) capacity values with similar to 100 % C.E. Furthermore, we report the results of testing a Li metal cell comprised of Li deposited HBCN anode and LiFePO4 (LFP) cathode.
Keywords: Boron carbon nitride; Dendrite-free Li metal anode; Functional scaffold; High temperature plating/stripping of Li; Molecular planarity parameter; X-ray micro-tomography

Template directed synthesis of boron carbon nitride nanotubes (BCN-NTs) and their evaluation for energy storage properties - Karbhal, Indrapal; Chaturvedi, Vikash; Yadav, Poonam; Patrike, Apurva; Shelke, Manjusha V. (Advanced Materials Interfaces, 2023)
A unique approach has been applied for the synthesis of 1D boron carbon nitride nanotubes (BCN-NTs) using MnO2 nanowires as templates. BCN-NTs have been evaluated in Na-ion batteries, Li-ion batteries, and supercapacitors as electrode material and exhibited excellent and stable electrochemical performance. BCN-NTs as an anode for Na-ion battery has been shown to be highly stable up to 3000 cycles with capacity retention of 95 mAh g(-1), at a high current density of 1 A g(-1). In the case of the Li-ion battery, these BCN-NTs show a specific capacity of 563 mAh g(-1) at a current density of 50 mA g(-1). Finally, when used as an electrode for a supercapacitor, BCN-NTs display a specific capacity of 221 F g(-1) at a current density of 3 A g(-1) and 168 F g(-1) even at a very high current density of 30 A g(-1) exemplifying the excellent rate performance. The multifunctionality and stable performance of BCN-NTs among various electrochemical energy storage systems highlight the robustness of the material and make it an excellent candidate for scalable production and commercialization.
Keywords: 1D-nanostructure; boron carbon nitride nanotubes (BCN-NTs); Co-doping; Li-ion battery; Na-ion battery; Supercapacitors

PANI-grafted boron, nitrogen co-doped carbon fiber: An outstanding, high-performance supercapacitor electrode - Nayan, Rajiv; Sinha, Shubhra; Dixit, Vaibhav; Satnami, Manmohan L.; Ghosh, Kallol K.; Pervez, Shamsh; Deb, Manas Kanti; Shrivas, Kamlesh; Rai, Manish K.; Yenchalwar, Sandeep G.; Wasnik, Kundan; Jadkar, Sandesh R.; et al. (JOURNAL OF ENERGY STORAGE, 2024)
Keywords: Composite; polyaniline; Solid-state supercapacitor